2020
DOI: 10.1186/s12875-020-01181-2
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ preferences in selecting family physician in primary health centers: a qualitative-quantitative approach

Abstract: Background: The role of family physicians (FPs) in the metropolitan area is critical in identifying risk factors for disease prevention/control and health promotion in various age groups. Understanding patients' preferences and interests in choosing a FP can be an effective and fundamental step in the success of this program. In this study factors affecting the FP selection by Iranian patients referred to health centers in the most populous areas in the south of Tehran were assessed and ranked. Methods: A sequ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 19 publications
(23 reference statements)
3
15
0
Order By: Relevance
“…On the other hand, evidence con rms that patients who have the option of choosing their personal doctor have more satisfaction with care precise and accurate diagnoses, putting enough time for medical examination, and availability and attendance of physician in health facility were among the main professional criteria which were mentioned by most of interviewees. In a similar study in the south of Tehran, Iran, Khatami and et al found that the most important factors in selecting FP were having specialist degree in family medicine, performing accurate examinations with receiving a detailed medical history and spending enough time to visit patients respectively (Khatami et al, 2020). In a study by Hoerger & Howard (1995), it was found that expertise was the rst priority for women to choose a doctor for prenatal care (Hoerger & Howard, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, evidence con rms that patients who have the option of choosing their personal doctor have more satisfaction with care precise and accurate diagnoses, putting enough time for medical examination, and availability and attendance of physician in health facility were among the main professional criteria which were mentioned by most of interviewees. In a similar study in the south of Tehran, Iran, Khatami and et al found that the most important factors in selecting FP were having specialist degree in family medicine, performing accurate examinations with receiving a detailed medical history and spending enough time to visit patients respectively (Khatami et al, 2020). In a study by Hoerger & Howard (1995), it was found that expertise was the rst priority for women to choose a doctor for prenatal care (Hoerger & Howard, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Continuity of care is associated with patient satisfaction, 19 while the cause of dissatisfaction may be attributed to frequent physician changes. 20 Patient satisfaction is defined as the degree to which the individual regards the health care service or product or the manner in which it is delivered by the provider as useful, effective, or beneficial. 21 It is a multidimensional concept that includes patient characteristics (age, gender, socioeconomic status, and patient's health status), health service provider characteristics (physician and other medical staff, emphasis on staff behavior, attitude to the patient, and communication), and the organizational aspects of health care organizations where the service is provided (emphasis on managing wait times: the period to get an appointment for the service and waiting time at the physician's office on the appointment).…”
Section: Discussionmentioning
confidence: 99%
“…Continuity of care is associated with patient satisfaction, 19 while the cause of dissatisfaction may be attributed to frequent physician changes. 20…”
Section: Discussionmentioning
confidence: 99%
“…Since 2005, the family physician program in Iran under the supervision of general practitioners has been proposed as the best option for reforming the health system, but its implementation was limited to villages and two provinces (Shiyani et al, 2016). Accordingly, it is essential to expand the FM program by setting up an FM specialty in the country to strengthen the healthcare with the optimized costs and to support patients' preferences to meet a specialist in primary care (Khatami et al, 2020). Although there is a difference in the health system between developed and developing countries, no single model for training residents to provide health services is found.…”
Section: Introductionmentioning
confidence: 99%